Novel catalysts for valorization of biomass to value-added chemicals and fuels - Lucas, Nishita; Kanna, Narasimha Rao; Nagpure, Atul S.; Kokate, Ganesh; Chilukuri, Satyanarayana V. (Journal of Chemical Sciences, 2014)
Key furan compounds such as 5-hydroxymethylfurfural (HMF), 2,5-furandicarboxylic acid (FDCA) and 2,5-dimethylfuran (DMF) were synthesized from renewable feedstocks. Dehydration of fructose was carried out in biphasic conditions employing several solid acid catalysts by targeting selective formation of HMF. Its selectivity is linearly dependent on total acidity clearly revealing that lower acidity favours selective formation of HMF. Oxidation and hydrogenolysis of HMF has been explored using 2 wt% Ru-K-OMS-2. The catalysts used for each transformation were subjected to detailed characterization using XRD, BET surface area, temperature-programmed desorption and transmission electron microscopy. The effect of various reaction parameters was also investigated for obtaining high yields of desired chemical intermediates. High FDCA yields of 93.4 mol% and 66 mol% were achieved in alkaline and base-free conditions, respectively. The 2 wt% Ru-K-OMS-2 is a versatile catalyst as it also catalyses HMF hydrogenolysis giving 33 mol% of DMF. Thus, utility of various novel materials as catalysts has been demonstrated in the multistep transformations of hexoses to furan-based fuels and chemicals.
Keywords: 2; 5-dimethylfuran; 5-furan dicarboxylic acid; 5-hydroxymethyl furfural; dehydration; fructose

Renewable fuels from biomass-derived compounds: Ru-containing hydrotalcites as catalysts for conversion of HMF to 2,5-dimethylfuran - Nagpure, Atul S.; Venugopal, Ashok Kumar; Lucas, Nishita; Manikandan, Marimuthu; Thirumalaiswamy, Raja; Chilukuri, Satyanarayana V. (Catalysis Science & Technology, 2015)
Production of transportation fuels from renewable biomass is hugely important considering the current ecological concerns over CO2 built up in the atmosphere. Ruthenium-containing hydrotalcite (HT) catalysts were applied for the selective hydrogenolysis of biomass-derived 5-hydroxymethylfurfural (HMF) to 2,5-dimethylfuran (DMF). Structural and morphological features of the catalysts were examined using various physico-chemical characterization techniques. The influence of various reaction parameters, such as reaction temperature, solvent, Ru content of the catalyst, etc., was investigated with respect to HMF conversion and DMF yield. The study clearly shows that well-dispersed Ru nanoparticles are highly active and selective in the conversion of HMF to DMF. A catalyst containing only 0.56 wt% Ru converted 100 mol% HMF to yield 58 mol% DMF. This catalyst was found to be recyclable as the activity was retained even after five cycles of reaction. 2-Propanol was found to be a good solvent as it helped to improve DMF yield through transfer hydrogenation. Based on the results of the investigations, a reaction pathway for the conversion of HMF to DMF was proposed for the present Ru-based catalyst system.

Highly efficient nitrogen-doped hierarchically porous carbon supported Ni nanoparticles for the selective hydrogenation of furfural to furfuryl alcohol - Kotbagi, Trupti V.; Gurav, Hanmant R.; Nagpure, Atul S.; Chilukuri, Satyanarayana V.; Bakker, Martin G. (RSC Advances, 2016)
Nickel nanoparticles supported on nitrogen doped hierarchically porous carbon (Ni/CN) are found to be highly efficient and reusable catalysts for the selective hydrogenation of biomass-derived furfural to furfuryl alcohol (FA). Various characterization methods were used to study the structural and morphological features of the catalysts. Furfural conversion of 96% and 95% FA selectivity was obtained using a 5 wt% Ni/CN catalyst. This catalyst showed excellent recyclability without any loss in activity and FA selectivity when it was reused four times. The higher catalytic performance is attributed to the nitrogen incorporated hierarchical porous 3D carbon network.

Hydrogenation of cinnamaldehyde to hydrocinnamaldehyde over Pd nanoparticles deposited on nitrogen-doped mesoporous carbon - Nagpure, Atul S.; Gurrala, Lakshmiprasad; Gogoi, Pranjal; Chilukuri, Satyanarayana V. (RSC Advances, 2016)
Palladium nanoparticles deposited on nitrogen-doped mesoporous carbon (NMC) were synthesized by simple ultrasonic-assisted method. This novel Pd-NMC catalyst was highly active and selective for the hydrogenation of cinnamaldehyde (CA) to hydrocinnamaldehyde (HCA) at room temperature (30 degrees C) under low H-2 pressure. The nitrogen-free mesoporous carbon (MC) and activated carbon (AC) were also employed as the support for Pd in the liquid-phase hydrogenation of CA. The incorporation of nitrogen into carbon matrix remarkably enhanced the catalytic activity and C=C bond hydrogenation selectivity (HCA selectivity of 93% with 100% CA conversion for Pd-NMC) in CA hydrogenation compared to the catalysts with no nitrogen (HCA selectivity of 66 and 47% for Pd-MC and Pd-AC, respectively). Moreover, Pd-NMC catalyst demonstrated an excellent recyclability without any loss in activity and HCA selectivity when it was reused for six times. The superior catalytic performance of Pd-NMC catalyst in CA hydrogenation is attributed to the small size of Pd nanoparticles due to presence of high nitrogen content (11.6 wt%) and mesoporous nature of NMC support.

Promotional effect of Fe on the performance of supported Cu catalyst for ambient pressure hydrogenation of furfural - Manikandan, Marimuthu; Venugopal, Ashok Kumar; Nagpure, Atul S.; Chilukuri, Satyanarayana V.; Raja, Thirumalaiswamy (RSC Advances, 2016)
A noble-metal free FeCu based bimetallic catalyst system prepared by facile co-impregnation method was found to be highly admirable for vapour phase selective hydrogenation of furfural to furfuryl alcohol at ambient pressure. Monometallic Cu/gamma-Al2O3, Fe/gamma-Al2O3 and bimetallic FeCu/gamma-Al2O3 catalysts with different Fe loadings were prepared. Structural and morphological features of the catalysts were thoroughly investigated by several physico-chemical characterization techniques. The influence of various reaction parameters, such as Fe loading, reaction temperature and flow of reactants was examined with respect to furfural conversion and furfuryl alcohol yield. The results clearly showed that an optimum amount of Fe is necessary to enhance the catalytic activity of monometallic Cu/gamma-Al2O3 for the selective hydrogenation of furfural. The catalyst FC-10 with 10 wt% Fe exhibited excellent activity which led to high furfural conversion (>93%) and furfuryl alcohol selectivity (>98%) under mild reaction conditions. The higher activity of bimetallic FeCu/gamma-Al2O3 compared to monometallic Cu/gamma-Al2O3 is ascribed to the formation of FeCu bimetallic particles and the existence of oxygen vacancies in the Fe oxide system. The superior activity after Fe loading on the Cu-based catalyst was attributed to the synergy between Cu and Fe. A plausible mechanism is proposed to explain the promoting effect of Fe, which involves synergism between Fe sites with strong oxophilic nature and Cu sites with a high ability for hydrogen activation. Based on the activity results, prolonged catalytic activity and spent catalyst analysis, the developed FeCu/gamma-Al2O3 catalyst is inexpensive, eco-benign and robust, which makes it a promising candidate for the efficient conversion of biomass-derived substrates to fine chemicals and drop-in biofuels.

Efficacy of clay catalysts for the dehydration of fructose to 5-hydroxymethyl furfural in biphasic medium - Lucas, Nishita; Nagpure, Atul S.; Gurrala, Lakshmiprasad; Gogoi, Pranjal; Chilukuri, Satyanarayana (Journal of Porous Materials, 2020)
5-Hydroxymethyl furfural (HMF) is one of the important platform chemical obtained from C6 sugars derived from biomass. The efficiency of montmorillonite clay catalysts (K-10, K-20, K-30, and Al pillared clay) has been systematically explored for the synthesis of HMF through dehydration of fructose in a biphasic solvent system. The catalysts were characterized by XRD, N(2)sorption,Al-27 MAS NMR,Si-29 NMR and FT-IR of chemisorbed pyridine. Acid treated K-10 catalyst was found to be the best among the clay catalysts tested. Various reaction parameters such as reaction temperature, catalyst content, solvent were optimized for achieving better yield of HMF. Under optimized reaction conditions, K-10 catalyst affords 80 mol% fructose conversion with HMF yield of 61 mol%. Insight into the type of acid sites essential for such cascade reactions has been furnished. Utilization of clay catalysts for HMF production will be beneficial to improve overall economics for the production of platform chemicals like HMF from biomass-derived raw materials.
Keywords: 5-hydroxymethyl furfural; Acidity; Clays; fructose; Insights

Insights into the catalytic activity of Ru/NaY catalysts for efficient H-2 production through aqueous phase reforming - Gogoi, Pranjal; Nagpure, Atul S.; Kandasamy, Prabu; Satyanarayana, C. V. V.; Raja, Thirumalaiswamy (Sustainable Energy & Fuels, 2020)
Ruthenium nanoparticles supported on NaY zeolite catalysts were synthesized by a simple ion exchange method. The structural and morphological features of the catalysts were systematically investigated using numerous techniques such as N-2-sorption, XRD, CO2-TPD, H-2-TPR, TEM, SEM, ICP-OES, TGA, CHN analysis, XPS, in situ CO-FTIR and NMR spectroscopy. These novel Ru-NaY catalysts were highly active and selective for H-2 production through aqueous phase reforming (APR) of glycerol and ethylene glycol. Among the various catalysts evaluated for H-2 production, the 3 wt% Ru-NaY catalyst demonstrated the highest catalytic performance with excellent H-2 selectivity and this catalyst exhibits better activity as compared to many state of the art catalysts reported so far. The superior catalytic activity of 3 wt% Ru-NaY was attributed to the appropriate Ru metal loading, good metal dispersion, small size of Ru nanoparticles, better metal-support interaction, and higher availability of catalytically active sites (Ru-0) and facilitated water gas shift (WGS) reaction. This catalytic activity result clearly shows that NaY zeolite supported Ru nanoparticles catalysts have excellent potential for H-2 production from biomass-derived compounds.

Novel Ru nanoparticle catalysts for the catalytic transfer hydrogenation of biomass-derived furanic compounds - Nagpure, Atul S.; Gogoi, Pranjal; Lucas, Nishita; Chilukuri, V. Satyanarayana (Sustainable Energy & Fuels, 2020)
The catalytic transfer hydrogenation (CTH) reaction was investigated for boosting the reduction of biomass-derived furanic compounds to obtain high-quality liquid biofuels. The CTH of 5-hydroxymethylfurfural (HMF) to 2,5-dimethylfuran (DMF) and furfural to 2-methylfuran (MF) was thoroughly studied over the Ru, Pd, Au, Pt, Ni, Rh and Cu metal catalysts supported on nitrogen-doped mesoporous carbons (NMCs) by utilizing 2-propanol as a source of hydrogen. The structural characteristics of the materials were examined by employing various physico-chemical methods, such as XRD, N(2)sorption, CHN analysis, XPS, FT-IR spectroscopy, H-2-TPR, TEM, CO2-TPD, ICP-OES and Raman spectroscopy. The influence of the N content, basicity of the catalyst, reaction temperature, hydrogen donor, nature of the catalyst support and transition metal was systematically investigated with regard to the substrate conversions and product yields. The correlation between the N content (wt%) of the catalysts and the Ru nanoparticle size (nm) and turnover frequency (h(-1)) was also investigated. Highly dispersed Ru nanoparticles (1.9 nm) supported on NMC displayed admirable catalytic performance in CTH for the conversion of HMF to DMF and furfural to MF. The catalyst Ru-NMC with a good N content (11.4 wt%) gave 84 and 87 mol% yields of DMF and MF, respectively, with 2-propanol as the source of hydrogen under mild reaction conditions. In addition, this catalyst demonstrated excellent recyclability. The better catalytic activity of the Ru-NMC catalyst in the CTH of HMF and furfural was credited to the small size of the Ru metal nanoparticles (1.9 nm), high N content, superior metal-support interaction and mesoporous framework of the catalyst.

Active and recyclable gold metal nanoparticles catalyst supported on nitrogen-doped mesoporous carbon for chemoselective hydrogenation of cinnamaldehyde to cinnamyl alcohol - Nagpure, Atul S.; Gogoi, Pranjal; Chilukuri, Satyanarayana V. (Chemistry-An Asian Journal, 2021)
Several supported gold metal catalysts with different Au nanoparticles sizes were prepared and evaluated for the chemoselective hydrogenation of cinnamaldehyde (CA) to cinnamyl alcohol (CAL). To investigate the structure-activity relationship, stability of catalyst, heterogeneity and recyclability, the structural characteristics of materials and Au catalysts (fresh and spent catalysts) were studied by employing variety of physico-chemical techniques. The interrelationship among Au nanoparticles size (nm) with turnover frequency (h(-1)) of Au catalysts has also been explored. Among the various Au catalysts tested, nitrogen-doped mesoporous carbon (NMC) supported Au catalyst having homogeneously dispersed (78.8%) Au nanoparticles (1.6 nm) synthesized by sol-immobilization method (Au-NMC-SI) demonstrated improved catalytic activity affording 78% CAL selectivity and 94.2% CA conversion without using any promoter. Moreover, Au-NMC-SI catalyst exhibited good recyclability and stability. The catalyst synthesis approach described in this investigation opens up a novel strategy for the design of highly efficient metal nano-catalysts supported on NMC materials.
Keywords: Au Nanoparticles; heterogeneous catalysis; Hydrogenation; Nitrogen-doped mesoporous carbon; Support-Metal interaction

Green synthesis of highly dispersed Cu metal nanoparticles catalysts - Nagpure, Atul S.; Mohture, Vikas M.; Kayarkar, Ankush (Inorganic Chemistry Communications, 2022)
Bionanotechnology approach for metal nanoparticles (NPs) synthesis is cost-effective and environmentally friendly. Organic molecules present in plant extracts can be efficiently utilized for bio-reduction of metal ions into metal NPs in a one-step green synthesis methodology. The biosynthesis procedure for metal NPs synthesis is quick, easy to scale up and can be perform at ambient conditions. The present investigations propose the biosynthesis of highly dispersed and stable copper NPs (Cu NPs) supported on NaY zeolite using plant extract of Tinospora cordifolia and Andrographis paniculata for the first time. The structural and morphological attributes of Cu NPs were explored by adopting various physico-chemical techniques, for example Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES), X-ray diffraction (XRD), Temperature Programmed Desorption (CO2-TPD and NH3-TPD), Temperature Programmed Reduction (H2-TPR), N2 sorption, Electron Microscopy (SEM, TEM and HR-TEM), X-ray Photoelectron Spectroscopy (XPS), etc. The experimental study (XRD, SEM, TEM, and HR-TEM) recommend that the green synthesis method by using plant extract has promising effect for the synthesis of nano-sized, stable and homogeneously dispersed Cu NPs catalysts (Cu NPs average size of 1.6 and 1.8 nm) as compared to chemical synthesis approach. The present result is better than those of many state-ofthe art techniques reported for green synthesis of Cu NPs using plant extract. According to the current study, it is advantageous to prepare highly dispersed metal NPs with desired size, shape, morphology and the required properties by using plant extract.
Keywords: Biosynthesis of nanomaterials; Cu nanoparticles; Heterogeneous catalysts; Support -Metal interaction; Zeolite supported catalysts

Investigation of structural and morphological insights of nanostructured layered double hydroxides: catalytic activity in aldol condensation - Bhagat, Shailesh K.; Nagpure, Atul S.; Lanjewar, Mamata R.; Gode, Nilesh G.; Thakare, Sanjay R. (Journal of Porous Materials, 2024)
Layered double hydroxides (LDHs) materials finds extensive applications in numerous fields such as medical science, industrial sector, agriculture and food, catalysis, polymers, nanotechnology, etc. The LDHs properties (structural, textural, morphological, spectroscopic and theoretical insights) can be design for achieving required materials for particular application in scientific areas. In the current investigation, we have synthesized mesoporous nanostructured LDHs materials via microwave, sonication and stirring method. The nanostructured LDHs was scientifically characterized by various physico-chemical techniques like XRD, N2 sorption, TGA, solid state one-dimensional 27Al magic angle spinning NMR spectroscopy, XPS, Raman Spectroscopy, FT-IR, ICP-OES, Electron Microscopy (SEM, FE-SEM, TEM and HR-TEM), EDX, elemental analysis, etc. On the basis of experimental study, it can be evidently witnessed that nanostructured LDHs materials was formed with good crystalline mesoporous nature. Solid state 27Al NMR showed single and sharp 27Al NMR signal at chemical shift value of + 1.4 ppm, strongly suggesting the presence of octahedral (Oh) AlO6 coordination site in all as-synthesized LDHs. Microwave and sonication techniques furnishes regularly dispersed well-developed flower-shaped nanocrystals however, stirring method gives mostly agglomerated nano-sized platelets. The mechanistic insights for the fabrication of nanostructures LDHs via microwave, sonication and stirring process were also highlighted. The different LDHs materials were utilized in the aldol condensation reaction of furfural with acetone for understanding structure-activity correlation. Microwave and sonication methodologies can be further exploited for the synthesis of many other inorganic-organic nanocomposites materials with stable and good dispersion of nanocrystals in addition to desired morphology and catalytic activity.
Keywords: Aldol condensation; catalysis; Flower-shaped nanocrystals; layered double hydroxides; Microwave and sonication techniques; Nanostructured materials

Synergistic effect of acidic-basic features of copper-doped layered double hydroxides nanocatalysts in valorization of biomass-derived furfural to biofuels - Gode, Nilesh G.; Nagpure, Atul S.; Rewatkar, Suresh B.; Bhagat, Shailesh K.; Deshmukh, Ganpat D.; Saini, Ajay (ChemPlusChem, 2025)
Valorization of biomass-derived chemicals into high-quality compounds and biofuels is enormously fundamental to diminish dependence on fossil-based resources. Furfural is a bio-based valuable compound which can be proficiently upgraded to 4-(2-furyl)-3-buten-2-one (FAc) and 1,4-pentadiene-3-one, 1,5-di-2-furanyl (F 2 Ac) via aldol condensation of furfural with acetone. In the present work, efficient Cu-doped Mg-Al layered double hydroxides (LDH) nanocatalysts are fabricated by coprecipitation and are exploited for furfural conversion to obtained FAc and F 2 Ac. The structure-activity relationship is scrutinized by characterizing fresh and spent nanocatalysts via numerous techniques. The good correlation between the amount of weak acidic-weak basic catalytic sites and nanocatalysts performance is established. The superior performance of Cu-0.1 nanocatalyst (Cu-content = 1.85 wt%) in aldol condensation is attributed to the presence of optimum weak acidic sites (0.21 mmol g-1) and weak basic sites (0.36 mmol g-1), synergistic acidic-basic effect, nano-sized Cu(OH) 2 nanoparticles (1.6 nm), high BET surface area (181 m2 g-1), and mesoporous architecture of material. Cu-0.1 nanocatalyst delivered 98% FAc selectivity with 100% furfural conversion at 85 degrees C. Furthermore, at 100 degrees C, the nanocatalyst gives 55% F 2 Ac selectivity with 73% furfural conversion. The catalyst displays good recyclability (7 recycles) and stability. Plausible mechanistic pathway for transformation of furfural to FAc and F 2 Ac is proposed.
Keywords: Aldol condensation; biofuels; biomass valorization; nanocatalysis; synergistic effect

Upgradation of biomass-derived furfural by nanostructured layered double hydroxides: Influence of stirring rate on structural features of materials - Bhagat, Shailesh K.; Nagpure, Atul S.; Lanjewar, Mamata R.; Gode, Nilesh G.; Deshmukh, Ganpat D.; Saini, Ajay (Inorganic Chemistry Communications, 2025)
The proficient conversion of biomass-derived compounds into the high-quality platform chemicals and bio-fuels is enormously imperative to decrease dependence on fossil feedstock. Furfural is a significant bio-based chemical which can be efficiently converted to valuable 4-(2-furyl)-3-buten-2-one (FAc) via aldol condensation. In this work, we have developed prominent layered double hydroxides (LDHs) catalysts for mild aldol condensation of furfural and acetone to acquired high performance with admirable FAc selectivity. Various nanostructured Mg-Al LDHs were synthesized through co-precipitation procedure under different stirring rate conditions. The structural, morphological and optical attributes of materials as well as recyclability aspect and structure-activity relationship was examined by characterizing the fresh and spent catalysts via numerous techniques (XRD, N2 sorption, DLS, CO2-TPD, NH3-TPD, FT-IR, UV-Visible spectroscopy, TGA, SEM, TEM, ICP-OES, 27Al NMR spectroscopy, XPS, Raman spectroscopy, etc). Several reaction parameters were also optimized. Among the catalysts tested, LDH-1200 catalyst exhibits outstanding performance by delivering 100% furfural conversion with 99% FAc selectivity. Moreover, catalyst illustrates excellent recyclability and stability. The mechanistic insight for aldol condensation was also investigated by monitoring the intermediates at different stages and intervals during the course of the reaction. This study confirms that stirring rate has significant influence on physico-chemical attributes of materials and the amount of weak basic sites plays imperative role in catalytic performance.
Keywords: Aldol condensation; Biomass-derived compounds; Flower-shaped nanocrystals; heterogeneous catalysis; Nanostructured mesoporous LDH